P Pengaruh Pemberian Pupuk Kotoran Sapi Terhadap Pertumbuhan dan Hasil Tanaman Kentang (Solanum Tuberosum L.) Varietas Granola: Pengaruh Pemberian Pupuk Kotoran Sapi Terhadap Pertumbuhan dan Hasil Tanaman Kentang (Solanum Tuberosum L.) Varietas Granola - Teftae, Oriensi Y.K; Noywuli, Nicolaus; Noa, Margareta; Simo, Daniel (Universitas Muhammadiyah Bengkulu, 2025)
Potatoes are a potential food crop to be cultivated because they contain carbohydrates, protein, minerals and vitaminsand are able to meet people’s demand for food supply. Demand for potatoes comes from household consumption, restaurant businesses and potato based indrustries. Apart from providing food needs, potato cultivation can support the community’s economy. Therefore, potato cultivation needs to continue to be carried out optimally. One of the problems with potato cultivation is the decreasing quality of the soil due to the tendency tu use inorganic fertilizers so that soil fertility decreases. The solution implemented is the application of organic materials to improve soil quality and provide plant nutrients. The purpose of writing this article is to determine the effect to appliying organic cow dung fertilizer on changes in soil quality and potato plant growth. The method used in this research is a qualitative method with literature study techniques.